Identity-based cross-domain authentication scheme in pervasive computing environments - LUO Chang-yuan; HUO Shi-wei; XING Hong-zhi (Tongxin xuebao)
An identity-based signature scheme was proposed based on additive elliptic curve group.The verification result of the signature was a constant with respect to the signer’s identity.The scheme could guarantee user anonymity in the process of cross-domain authentication and avoided the pairing operation.Then a cross-domain authentication scheme was constructed by combining the proposed signature scheme.During the authentication,a user constructed the signature of timestamp as authentication proof,which realized secure cross-domain authentication and user anonymity.It is shown that the proposed scheme has superiority in both security and efficiency,and is more suitable for pervasive computing.